2022
DOI: 10.1101/2022.10.26.513850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide screening reveals metabolic regulation of translational fidelity

Abstract: Translational quality control is critical for maintaining the accuracy of protein synthesis in all domains of life. Mutations in aminoacyl-tRNA synthetases and the ribosome are known to affect translational fidelity and alter fitness, viability, stress responses, neuron function, and life span. In this study, we used a high-throughput fluorescence-based assay to screen a knock-out library of Escherichia coli and identified 30 nonessential genes that are critical for maintaining the fidelity of stop-codon readt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 71 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…Mutations in uS12 that lead to Str resistance often improve ribosomal fidelity, which counters the effect of Str to induce mistranslation (32,33). Deleting rsmG also increases ribosomal fidelity in E. coli and M. tuberculosis (27,34). Using a dual-fluorescence reporter that our lab previously developed (35,36), we found that the Salmonella ΔrsmG strain exhibited decreased readthrough of UGA stop codons (Fig.…”
Section: Rimp Enhances Mistranslation In the Presence Of Strmentioning
confidence: 92%
“…Mutations in uS12 that lead to Str resistance often improve ribosomal fidelity, which counters the effect of Str to induce mistranslation (32,33). Deleting rsmG also increases ribosomal fidelity in E. coli and M. tuberculosis (27,34). Using a dual-fluorescence reporter that our lab previously developed (35,36), we found that the Salmonella ΔrsmG strain exhibited decreased readthrough of UGA stop codons (Fig.…”
Section: Rimp Enhances Mistranslation In the Presence Of Strmentioning
confidence: 92%
“…The connection between metabolism and translational fidelity is further revealed by a recent genetic screening [ 73 ]. In a genome-wide screening of an E. coli knockout library, we have identified several genes that control metabolic processes to affect stop-codon readthrough.…”
Section: Translational Fidelity During Bacterial Stressesmentioning
confidence: 99%
“…In particular, CyaA controls the synthesis of cyclic AMP, which is a master regulator of metabolic pathways [ 74 ]. We show that deleting cyaA decreases readthrough of stop codons, at least partially by repressing the expression of tRNAs that compete with release factors [ 73 ]. It is possible that amino acid imbalance may also contribute to the efficiency of readthrough.…”
Section: Translational Fidelity During Bacterial Stressesmentioning
confidence: 99%
See 2 more Smart Citations